Electrical and electronic waste management: a case study in University of Duhok, Iraq - Rafia, Afroz (World Academic Publishing, 2013)
The aim of this paper is to investigate the perception, knowledge and attitude of the households towards electrical and electronic equipment waste (e-waste) management in Duhok city, Iraq. It also tried to identify current e-waste management practiced by households in Duhok. It has been found in this study that much of the electrical and electronic equipment was updated within two thirds of their designed lifetime. Most of the respondents informed that they just threw their e-waste to the waste bin. It can be concluded that all stakeholders of e-waste management, from the government and nongovernmental sectors should consider shifting the management options towards the top of the waste management hierarchy (prevention and waste minimization) by substituting the hazardous materials in e-waste and encouraging redesign of equipment for a better control of the negative impacts of e-waste.